Filmmusikken i Nanook of the North: fra kompilasjon til partitur - Skare, Roswitha (Nordlit, 2012)
The article starts with the film's premiere in New York in 1922. With help of 2 cuesheets - probably compiled in 1922 - the music of one scene ("Winter") is examined, before the article takes a look into 2 original scores composed by Stanley Silvermanand Timothy Brock for either VHS or DVD editions of the film. It turns out that these original scores give much more priority to the pictures than the music that probably accompanied Nanook in 1922. One explanation for this might be found in the different experiences of today's audiences concerning film in general and film music in particular.